Efficient removal of Congo Red dye using MoS2-modified Mg-Al LDH nanocomposites for efficient wastewater remediation - Kumar S.; Bar A.; Sarkar S.; Singh J.; Upadhyay C. (My University, 2025)
Recently, 2D materials have gained significant attention for their promising applications in water remediation, attributed to their exceptional structural and chemical properties. The Mg-Al LDH and MoS2/Mg-Al LDH composites were synthesized using hydrothermal method and applied for the removal of Congo Red dye from wastewater. The Transmission Electron Microscopy (TEM) and Scanning Electron Microscopy (SEM) confirms the successful formation of Mg-Al LDH hexagonal sheets on the surface of MoS2 petals like structure, while Fourier Transform Infrared Spectroscopy (FTIR) was employed to investigate the functional group present in each sample. The adsorption efficiency of Mg-Al LDH and MoS2/Mg-Al LDH composites was 56.2 and 116.41 mg/g. Adsorption studies revealed that the MoS2/Mg-Al LDH composite exhibited excellent adsorption performance compared to MgAl LDH, with a maximum adsorption capacity of 116.41 mg/g. The adsorption behavior of Congo Red dye onto Mg-Al LDH and MoS2/Mg-Al composite was better described by the kinetic pseudo 2nd order model and conformed to the Langmuir isotherm model. The thermodynamics studies reveal that the uptake of Congo Red dye on MoS2/Mg-Al LDH nanocomposite followed a spontaneous and endothermic process. The superior adsorption capability is due to the electrostatic interaction between Congo Red dye with the MoS₂/Mg-Al LDH composite surface, as well as anion exchange between the Congo Red dye and the composite. These findings suggest that MoS2/Mg-Al LDH composite is emerging as a superior candidate for practical application in removing dye pollutants from wastewater. © 2025